The Expiry of a Mandate of a Member of the Management Board and its Influence on Third Person’s Tax Liabilty. Commentary on Supreme Administrative Court Judgement of 25 March 2013, I FSK 521/12 - Olesiak, Jarosław (Journal of Finance and Financial Law, 2015)
The essay refers to the tax liability of members of board for company’s tax arrears. Under the Polish law that kind of liability arises from decision issued in tax proceedings in which tax authorities are obliged to verify the party’s status. The regulation of the burden of proof is based on two principles: tax authority needs the evidence of party’s membership in a board, while a party needs to prove that a petition to declare bankruptcy was filed or proceedings were instituted in order to avoid declaration of bankruptcy in due time, or party is not liable for the failure to file a petition to declare bankruptcy or to institute proceedings in order to avoid declaration of bankruptcy. If the party’s membership in board is disputable, the tax authority may be obliged to request a general court to determine whether or not that kind of legal relationship exists.